2005
DOI: 10.1097/01.hjh.0000188732.52722.5a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genes related to immune tolerance and inflammation (tumour necrosis factor-α, interleukin-6) on blood pressure, protein excretion and oedema in pregnancy

Abstract: We demonstrate in a large population that common maternal polymorphisms of genes related to immune tolerance and inflammation are associated with blood pressure regulation, urinary protein excretion and oedema during pregnancy. The analysed polymorphisms seem to contribute to the multifactorial pathogenesis of gestational hypertension and pre-eclampsia. The findings support the hypothesis that genetically determined factors of maternal immune tolerance play a role in the pathogenesis of hypertensive disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Although considerable efforts have been made in recent years to identify the genes responsible for the development of preeclampsia, and many genes have been identified, including angiotensinogen (5), the type 1 and type 2 angiotensin receptors (6,7), tumor necrosis factor a (8), endothelial nitric oxide synthase (9), methylene tetrahydrofolate reductase (10), and the Leiden variant of coagulation factor V (11), the results have not been consistently reproducible. Recent two studies in a large population suggested that polymorphisms of angiotensinogen gene and immune tolerance and inflamation related genes (tumour necrosis factor-a and interlenkin-6) might play a role in pathogenesis of gestational hypertension and preeclampsia (12,13),supporting some of the above findings.…”
Section: Introductionmentioning
confidence: 66%
“…Although considerable efforts have been made in recent years to identify the genes responsible for the development of preeclampsia, and many genes have been identified, including angiotensinogen (5), the type 1 and type 2 angiotensin receptors (6,7), tumor necrosis factor a (8), endothelial nitric oxide synthase (9), methylene tetrahydrofolate reductase (10), and the Leiden variant of coagulation factor V (11), the results have not been consistently reproducible. Recent two studies in a large population suggested that polymorphisms of angiotensinogen gene and immune tolerance and inflamation related genes (tumour necrosis factor-a and interlenkin-6) might play a role in pathogenesis of gestational hypertension and preeclampsia (12,13),supporting some of the above findings.…”
Section: Introductionmentioning
confidence: 66%
“…We have seen evidence that preeclamptic women with the TNF-α 308A genotype exhibit higher blood pressure and urinary protein excretion. This may play an important role in the etiology of gestational hypertension and PE [36,37]. Furthermore, severe IUGR-complicated PE was observed more frequently in carriers of the rs1800629 allele A [35].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting outcome is variable clinical phenotypes, e.g. increased proteinuria, fetal growth restriction, severe PE or preterm labor [36,37,64,65]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 As a single polymorphism most probably accounts only for a small part of the multifactorial pathogenesis of hypertensive disorders of pregnancy, it may be hard to detect its effect when focusing on binary end points such as gestational hypertension or preeclampsia. In contrast, the analysis of markers such as blood pressure (BP) elevation, protein excretion and oedema during pregnancy might be able to detect small but significant genetic effects.…”
Section: Introductionmentioning
confidence: 99%